2021
DOI: 10.1002/bkcs.12441
|View full text |Cite
|
Sign up to set email alerts
|

Detection of benzalkonium chloride on glass surfaces using silver nanoparticles

Abstract: Raman reporter‐based surface‐enhanced Raman scattering (SERS) has been used to investigate the detection of one member of a class of the cationic surfactant quaternary ammonium compounds, alkyl dimethyl benzyl ammonium chloride, also known as benzalkonium chloride (BAC). For this study, SERS was performed using silver nanoparticles (AgNPs). Density functional theory (DFT) of BAC on Ag6 clusters was introduced to estimate binding at the level of the B3LYP/LANL2DZ basis sets. As the chain length increased from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…The DFT approach is increasingly used for SERS spectroscopy by several research groups, as demonstrated by the most recent studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] in which close links between DFT calculations and SERS applications are shown. Among these studies, the following studies devoted to applications in sensors, especially for environmental protection, and to applications in biomedicine, are worthy of particular attention.…”
Section: Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DFT approach is increasingly used for SERS spectroscopy by several research groups, as demonstrated by the most recent studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] in which close links between DFT calculations and SERS applications are shown. Among these studies, the following studies devoted to applications in sensors, especially for environmental protection, and to applications in biomedicine, are worthy of particular attention.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…However, because BAC potentially poses risks for human and environmental safety, it is necessary to know the benefits versus the risks of a very extensive use of BAC use in commercial products. Hence, in this paper [ 59 ], an efficient and sensitive SERS method to rapidly detect BAC adsorbed on glass surfaces was employed by using AgNP nanostructures. In this regard, DFT calculations lent valid support to the SERS technique for detecting very low amounts of BAC along with providing significant information on the properties of BAC and its adsorption on metal.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…[13][14][15] To achieve this goal, however, it is crucial to fabricate nanostructures that are capable of forming controllable nanogaps since the electromagnetic enhancement of the incident light is achieved using hot spots created in nanogaps of less than 10 nm diameter. [16][17][18] Recently, tau-381 was detected with high sensitivity via plasmonic coupling effects using the aggregation of gold nanoparticles (AuNPs). 19 However, as described in detail later in this text, the reproducibility is poor in the case of AuNPs aggregated by electrostatic interactions because the nanogaps between the AuNPs cannot be controlled uniformly.…”
Section: Introductionmentioning
confidence: 99%